TSC22D4 is a molecular output of hepatic wasting metabolism. Issue 2 (11th January 2013) - Jones, Allan; Friedrich, Kilian; Rohm, Maria; Schäfer, Michaela; Algire, Carolyn; Kulozik, Philipp; Seibert, Oksana; Müller‐Decker, Karin; Sijmonsma, Tjeerd; Strzoda, Daniela; Sticht, Carsten; Gretz, Norbert; et al.
Abstract In mammals, proper storage and distribution of lipids in and between tissues is essential for the maintenance of energy homeostasis. Here, we show that tumour growth triggers hepatic metabolic dysfunction as part of the cancer cachectic phenotype, particularly by reduced hepatic very‐low‐density‐lipoprotein (VLDL) secretion and hypobetalipoproteinemia. As a molecular cachexia output pathway, hepatic levels of the transcription factor transforming growth factor beta 1‐stimulated clone (TSC) 22 D4 were increased in cancer cachexia. Mimicking high cachectic levels of TSC22D4 in healthy livers led to the inhibition of hepatic VLDL release and lipogenic genes, and diminished systemic VLDL levels under both normal and high fat dietary conditions. Liver‐specific ablation of TSC22D4 triggered hypertriglyceridemia through the induction of hepatic VLDL secretion. Furthermore, hepatic TSC22D4 expression levels were correlated with the degree of body weight loss and VLDL hypo‐secretion in cancer cachexia, and TSC22D4 deficiency rescued tumour cell‐induced metabolic dysfunction in hepatocytes. Therefore, hepatic TSC22D4 activity may represent a molecular rationale for peripheral energy deprivation in subjects with metabolic wasting diseases, including cancer cachexia.